Preliminary Molecular Study of Chloramphenicol Anchoring on Laccase Enzyme from Trametes hirsuta - Riyanto, Hanzhola Gusman; Sanjaya, Afiten Rahmin (Makara Journal of Science, 2024)
Antibiotics are one of emerging pollutants generally emitted from livestock production and the food industry to the environment. The presence of this pollutant could initiate the development of resistant bacteria that can be fatal to human health. The degradation of antibiotics using enzymes or microbe could be an alternative because the residue or intermediate product is less harmful than of the conventional method. This research aims to support a preliminary study of the degradation of antibiotics using enzyme through molecular docking via Molecular Operating Environment software and molecular dynamics (MD) study via CABSFLEX 2.0 and WebGro macromolecular simulations. The molecular docking of the laccase-chloramphenicol complex has low binding energies of approximately −8.1350 and −8.2290 kcal/mol for both rigid and flexible methods, respectively, indicating that the formation of the complex is advantegous. MD simulation further revealed a decrease in rigidity after the interaction with the ligand. Hydrogen bonding analysis indicated up to five hydrogen bonds in the complex, underscoring the robustness of the enzyme--ligand interaction. These results collectively contribute to our understanding of the efficacy of enzyme-mediated antibiotic degradation and emphasize the potential for this approach to mitigate environmental and health concerns associated with antibiotic pollution